(untitled) (Jurnal Ilmiah Teknik Sipil, 2026)
Structural design for multistory buildings must satisfy not only strength and safety requirements but also material efficiency to achieve cost-effective construction. This study aims to redesign the structural system of Building A of the Kiara Beach Front Apartment to obtain a more efficient design while maintaining structural performance and safety. The redesign was carried out using the Special Moment Resisting Frame (SMRF) system in accordance with the provisions of SNI 1726:2019, SNI 1727:2020, and SNI 2847:2019. A three-dimensional structural model was developed in SAP2000, followed by analyses of gravity and seismic loads, inter-story drift, structural irregularities, and the design of beams, columns, slabs, and foundations. The results indicate that the redesigned structure satisfies seismic performance requirements, with the fundamental period and inter-story drift remaining within the allowable limits specified by the applicable standards. Furthermore, the optimization of structural member dimensions and reinforcement improved material efficiency in the first-floor structural elements, resulting in an 11% reduction in concrete volume and a 23% reduction in reinforcement weight. Consequently, a more economical structural design was achieved without compromising structural safety requirements.